Jerusalem's zions - Wharton, Annabel Jane (Material religion, 2013)
The human desire to embody the sacred, to give it a physical place and a material form, is nowhere better demonstrated than in Jerusalem. As one of the world's oldest continuously occupied, politically contested and religiously invested cities, Jerusalem's natural and architectural landscape has been overlaid with scripture and interpreted to death. This paper examines one site of this phenomenon: Mount Zion. "Zion" is often used synecdochically, as a part of Jerusalem standing in for the whole of the city. But "Zion" has also acted as a toponym for the ancient citadel of David. This specific piece of real estate shifted its location in antiquity in order to retain its biblical associations, inciting innocent and not-so-innocent claims of holiness where holiness may not belong.